GHRL as a prognostic biomarker correlated with immune infiltrates and progression of precancerous lesions in gastric cancer - Wang, Jinyun; Liu, Dingwei; Xie, Yong (Frontiers in Oncology, 2023)
Objective Ghrelin is a protein that regulate appetite and energy balance in the human body, which is encoded by the ghrelin prepropeptide gene (GHRL). GHRL is linked with carcinogenesis and immune regulation. However, the correlation of GHRL to prognosis and tumor-infiltrating lymphocytes in gastric cancer (GC) remains unclear. Methods In this study, we assessed the transcriptional expression, prognosis, and different clinicopathological features about GHRL and the correlation between GHRL and tumor infiltration immune cells in GC patients based on the data published in the following databases: TIMER, GEPIA, GEO, STRING, UALCAN, TISIDB, and Kaplan–Meier Plotter. Furthermore, R software analysis for GC Correa’ cascade was also provided. Finally, GHRL expression in GC tissues was assayed using quantitative real-time polymerase chain reaction and immunohistochemistry. Results We found that GHRL expression in GC samples was lower than in normal samples and verified by quantitative PCR (qPCR) and immunohistochemistry. However, sample type, cancer stage, and worse survival were correlated to high GHRL expression. We also found that the expression of GHRL in dysplasia was significantly lower than that in CNAG and in GC. High GHRL expression was connected with immunomodulators, chemokines, and infiltrating levels of B cells, CD8+ T cells, CD4+ T cells, macrophages, neutrophils, and dendritic cells in GC. Conclusions GHRL is a prognostic biomarker for GC patients, and it is correlated with progression of precancerous lesions in GC. It might lead to poor prognosis by regulating tumor immune microenvironment. Studies are important to explore therapeutic targeting GHRL in the future.